Based on a family of bi-univalent functions introduced through the Faber polynomial expansions and Noor integral operator - F. Müge Sakar; Arzu Akgül (AIMS Mathematics, 2022)
In this study, by using q-analogue of Noor integral operator, we present an analytic and bi-univalent functions family in D. We also derive upper coefficient bounds and some important inequalities for the functions in this family by using the Faber polynomial expansions. Furthermore, some relevant corollaries are also presented.